A new species of the genus Ceriodaphnia Dana, 1853 (Cladocera: Daphnidae) from Eastern Siberia (Russia) that combines morphological features of two species groups - Garibian, Petr G.; Andreeva, Lena V.; Kotov, Alexey A. (Zootaxa, 2023)
Taxa of the genus Ceriodaphnia Dana, 1853 (Cladocera: Daphniidae) are ubiquitous in temperate and tropical lakes, and the taxonomy of the genus is confused. Moreover, present keys are often regional and insufficient for the taxonomic assignment of species at a global scale. This communication is aimed at improving our understanding of the C. dubia s.l. species group. We redescribe C. dubia s.l. from Northern Eurasia and describe a new species from Central Yakutia (Eastern Siberia, Russia). In contrast to typical members of the C. dubia group, C. nikolaii sp.nov. has the postabdomen of the parthenogenetic female with preanal margin slightly or strongly projecting and angulated. Moreover, adult males have a pronounced preanal angle and sensory seta of antenna I which is shorter than the longest easthetasc. Our finding challenges current definitions of species groups in Ceriodaphnia. Indeed, a postabdomen shape with a strongly projected preanal angle is characterstic of another group of this genus, namely the C. laticaudata-group. We found a taxon that combines the diagnostic morphological characters of two species groups. Further development of the genus taxonomy must be accompanied by redescriptions of all well-accepted and dubious taxa from their type localities and revisions of populations from other localities of the world.